THE IMPACT OF TAX LITERACY OF THE POPULATION ON THE EFFICIENCY OF USING DIGITAL TAX SERVICES - Xatamov Alishеr Farxadovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article examines the impact of tax literacy of the population on the efficiency of using digital tax services. In the context of rapid digital transformation, tax administrations increasingly rely on electronic platforms to improve service delivery, reduce administrative costs, and enhance compliance. However, the effectiveness of these systems largely depends on taxpayers’ knowledge and ability to use digital tools. The study analyzes the relationship between tax literacy, user behavior, and key efficiency indicators such as adoption rate, accuracy of reporting, and compliance level. Based on analytical methods and a review of international practices, the research highlights the importance of improving tax literacy to ensure broader participation and more effective functioning of digital tax systems. The findings support a constructive approach focused on education, accessibility, and user-oriented service design.